3D interaction design and application development - Lim, Kian Teck (2008)
Human-computer interaction (HCI) is an area concerned with the design, evaluation and implementation of interactive computing systems for human use. A 3D environment makes use of the HCI to provide visual and tactile interaction to the user. However the HCI hardware devices and software development are expensive. Hence it is essential to explore an affordable solution for HCI that can be implemented for educational and research uses.